International Pediatric MS Study Group Global Members Symposium report. (30th August 2016) - Wassmer, Evangeline; Chitnis, Tanuja; Pohl, Daniela; Amato, Maria Pia; Banwell, Brenda; Ghezzi, Angelo; Hintzen, Rogier Q.; Krupp, Lauren B.; Makhani, Naila; Rostásy, Kevin; Tardieu, Marc; Tenembaum, Silvia; et al.
Abstract : The International Pediatric Multiple Sclerosis Study Group held its inaugural educational program, "The World of Pediatric MS: A Global Update, " in September 2014 to discuss advances and challenges in the diagnosis and management of pediatric multiple sclerosis (MS) and other neuroinflammatory CNS disorders. Highlights included a discussion on the revised diagnostic criteria, which enable the differentiation of MS, acute disseminated encephalomyelitis, neuromyelitis optica, and other neuroinflammatory disorders. While these criteria currently identify clinical and MRI features for a particular diagnosis, advances in biomarkers may prove to be useful in the future. An update was also provided on environmental factors associated with pediatric MS risk and possibly outcomes, notably vitamin D deficiency. However, optimal vitamin D intake and its role in altering MS course in children have yet to be established. Regarding MS outcomes, our understanding of the cognitive consequences of early-onset MS has grown. However, further work is needed to define the course of cognitive function and its long-term outcome in diverse patient samples and to develop strategies for effective cognitive rehabilitation specifically tailored to children and adolescents. Finally, treatment strategies were discussed, including a need to consider additional drug treatment options and paradigms (escalation vs induction), although treatment should be tailored to the individual child. Of critical importance, clinical trials of newer MS agents in children are required. Although our understanding of childhood MS has improved, further research is needed to have a positive impact for children and their families.